CERTYFIKACJA ZNAJOMOŚCI JĘZYKA POLSKIEGO JAKO OBCEGO WE WŁOSZECH: PROBLEMY, WYZWANIA, POSTULATY - Marzec, Urszula; Marzec, Małgorzata (Neofilolog, 2019)
The article contributes to the discussion regarding the state certificate Since the new legislation in 2015 was introduced, the number of foreign sessions of the state certificate examinations in Polish as a foreign language has significantly decreased. The article aims to show the impact of the amended legal provisions on the availability of the certificate examinations outside of Poland and, consequently on the level of knowledge about them among potential candidates in Italy. The article is based on the results of the survey conducted by the authors among the students of Polish studies in Italy.